Relationship Between Self-Efficacy and Students' Learning Interest with Gender as a Moderator - Zaenariyah, Zaenariyah (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2024)
Students' learning interest must be continuously nurtured so that their learning interest will increase. However, along with the rapid advancement of technology, it can have a negative impact on students' learning interest. High learning interest can encourage students to devote attention, energy and time to learning activities, thereby improving the quality of the learning process and outcomes. The purpose of this study was to determine whether there is a relationship between self-efficacy and students' learning interest with gender as a moderator at MA Darussholihin NW Kalijaga. This study uses a quantitative approach using correlational and comparative methods. The measuring instruments in this study are aspects of learning interest according to Hurlock which are adapted from Pangestuti's research in 2012. and a self-efficacy scale compiled based on aspects of efficacy according to Bandura which are adapted from Hasin's research in 2018. The number of samples is 96 students. Sampling was carried out using the purposive sampling method. The results of the study showed that the significance value of the learning interest variable and the self-efficacy variable was 0.00 <0.05, so the variables were said to be correlated. The correlation level between variables was 0.522, so the variables were said to be correlated. While the description of the level of learning interest of male and female students obtained a sig. value of 0.011> 0.05, so the average value of learning interest of male and female students was the same.